Passive acoustic monitoring gives new insight into year-round duetting behaviour of a tropical songbird - Paweł Szymański (Elsevier, 2021)
Passive acoustic monitoring (PAM) allows for cost-effective, unattended and non-invasive acoustic sampling over an extended period of time and is now an invaluable tool for acoustic monitoring of vocally active species. Its application is rapidly growing in studies covering multiple aspects of avian ecology and behaviour, including presence-absence surveys, population density estimations, threatened species monitoring and anthropogenic impacts on populations. However, the potential for information on year-round variation in male and female vocalisations and the factors affecting duetting behaviour to be derived from PAM has never been exploited. In the present study we deployed automatic recording units (ARU) to investigate long-term sex-specific life strategies based on the vocal activity of the Yellow-breasted Boubou Laniarius atroflavus, an Afromontane, duetting songbird. Using automatic detection we showed strong seasonality in singing performance with males producing solo songs at a higher rate during the breeding than non-breeding season whereas female solos peaked at the end of the breeding season. Duets were produced at a relatively stable rate throughout the year except the time encompassing the turn of the rainy and dry seasons when overall vocal activity was at a low level. In general, year-round singing patterns coincided with the rainy and dry seasons at the study site with vocal activity peaking in the dry season and gradually declining with the onset of rainfall. In addition, we found that boubous were slightly more vocally active when morning temperature was higher, especially in the rainy season. Sex-dependent variation in vocal activity in relation to life cycle stage may suggest that differences between males and females are of functional significance. Most likely, the seasonality of male solo songs could be explained on the basis of sexual selection pressure and that male and female joint vocalizations act as a cooperative behaviour playing a role in territory defence against conspecifics. Our PAM-based results provide new and important insights into how male–female solo songs and duet interactions may be related to year-round territoriality. This may help us to better understand the evolutionary significance of duetting. Furthermore, our findings highlight the link between life cycle events of a tropical songbird and seasonal changes in weather conditions. By tracking the effect of weather on vocal activity, PAM might provide an important indication of how changes in climate may affect bird behaviour.